Suspended particulate layers and internal waves over the southern Monterey Bay continental shelf: An important control on shelf mud belts?. Issue 1 (21st January 2014) - Cheriton, Olivia M.; McPhee‐Shaw, Erika E.; Shaw, William J.; Stanton, Timothy P.; Bellingham, James G.; Storlazzi, Curt D.
<x xml:space="preserve">Abstract</x> [1] Physical and optical measurements taken over the mud belt on the southern continental shelf of Monterey Bay, California documented the frequent occurrence of suspended particulate matter features, the majority of which were detached from the seafloor, centered 9–33 m above the bed. In fall 2011, an automated profiling mooring and fixed instrumentation, including a thermistor chain and upward‐looking acoustic Doppler current profiler, were deployed at 70 m depth for 5 weeks, and from 12 to 16 October a long‐range autonomous underwater vehicle performed across‐shelf transects. Individual SPM events were uncorrelated with local bed shear stress caused by surface waves and bottom currents. Nearly half of all observed SPM layers occurred during 1 week of the study, 9–16 October 2011, and were advected past the fixed profiling mooring by the onshore phase of semidiurnal internal tide bottom currents. At the start of the 9–16 October period, we observed intense near‐bed vertical velocities capable of lifting particulates into the middle of the water column. This "updraft" event appears to have been associated with nonlinear adjustment of high‐amplitude internal tides over the mid and outer shelf. These findings suggest that nonlinear internal tidal motions can erode material over the outer shelf and that, once suspended, this SPM can then be transported shoreward to the middle and shallow sections of the mud belt. This represents a fundamental broadening of our understanding of how shelf mud belts may be built up and sustained.